The effects of monetary policy surprises on net wealth inequality in Portugal: the housing market channel - Issá, David Elias Ribeiro (2022)
We study the transmission of monetary policy shocks in wealth inequality in Portugal, via the housing market channel. We compute the impulse response functions (IRFs) of mortgage interest rates, housing and rental prices, after surprises in both an aggregate and two dismembered policy instruments corresponding to the Target Rate and Forward Guidance components of monetary policy. These effects are distributed across individual households through a microdata simulation using the Household Finance and Consumption Survey. We find that the rise in house prices and the decline in mortgage rates and rental prices following the policy shocks all positively contribute to a redistribution of wealth, with the overall wealth redistribution being greatly felt at the extreme deciles of the distribution.